REORGANIZACIÓN DE LA CONTABILIDAD EN LA ASOCIACIÓN CAJA DE AHORRO Y CRÉDITO “SAN FRANCISCO” DE LA PARROQUIA CHANGAIMINA, CANTÓN GONZANAMÁ, PROVINCIA DE LOJA. PERIODO DEL 01 DE SEPTIEMBRE AL 31 DE DICIEMBRE DEL 2017 - Ojeda Betancourt, Carmita Cecilia (2018)
The thesis work called REORGANIZATION OF ACCOUNTING IN THE ASSOCIATION OF SAVINGS AND CREDIT "SAN FRANCISCO" OF THE PARISH CHANGAIMINA, CANTON GONZANAMÁ, PROVINCE OF LOJA. PERIOD FROM 01 SEPTEMBER TO DECEMBER 31, 2017., was developed with the purpose of knowing the economic and financial situation of the Savings and Credit Fund and being able to make the appropriate decisions in the control and management of its financial resources To comply with the objectives, the Accounts Plan and Accounts Manual of the Single Catalog of Accounts of the Superintendency of Economy, Popular and Solidarity was considered, in which each of the accounts and sub-accounts of the asset, liability, equity, income and expenses, then the description, movement and balance of each of the accounts is disclosed. Then the physical verification of all values, assets, rights and obligations was made, allowing the initial inventory to be prepared with an Asset of $ 150,300.28, a Liability of $ 109,163.35 and the Equity of $ 41,136.93, reflecting these values in the Initial Situation Status. In addition, the auxiliary records were designed, for its fulfillment the source documentation was necessary, which served as a means of controlling the information in a detailed manner that simplifies and facilitates the registration and accuracy of the values; With the help of the documentation supporting the daily movement, the memorandum of operations was 5 prepared, which allowed the accounting process to be developed from the recording of operations in the main books to the structuring of the financial statements, in the Income Statement it reflects income from $ 8,903.57, expenses of $ 8,082.76, of which a profit of $ 820.81 is obtained; the Statement of Financial Position discloses an Asset of $ 157.758,25, a Liability of $ 115,188,51 and a Net Worth of $ 42,569.74; the Statement of Cash Flows reveals the Operating Activities of $ 10,456,57, the Investment Activities of $ 0.00 and the Financing Activities of $ 612.00 with a positive balance of $ 11,068,57, demonstrating that the Both administrative and operational activities carried out by the Savings and Credit Fund are profitable in the last four months of the economic year. Once the accounting process was completed, it was possible to obtain the conclusions and recommendations, it was found that it did not have an adequate accounting process which does not allow it to know the economic situation in which the entity is located, therefore the manager is recommended to keep an accounting in a permanent manner that allows you to obtain timely and reliable financial information, aimed at making decisions so that you progress in each of the activities you perform.